Johannes Brenz and the Problem of Ecclesiastical Discipline - Estes, James Martin (Church history, 1972)
Ecclesiastical discipline is the one area of church order in which Johannes Brenz, one of the most important architects of the sixteenth-century Lutheran territorial state church, signally failed to achieve his purposes.1 During his career in Schwäbisch Hall (1522–1548) and later in Württemberg (1550–1570) Brenz tried repeatedly, but ultimately without success, to establish an order of ecclesiastical discipline which would include effective use of the penalty of excommunication. An examination of the reasons for this failure may throw some light on the limits of what could be achieved within the context of the state church.